TEACHERS’ ELICTATION TECHNIQUES IN ENGLISH CLASSROOM INTERACTION AT SMK NEGERI 13 MEDAN - Khairiana Fitri; Neni Afrida Harahap; Johannes Jefria Gultom (Universitas Negeri Medan, 2021)
TEACHERS’ ELICTATION TECHNIQUES IN ENGLISH CLASSROOM INTERACTION AT SMK NEGERI 13 MEDAN *Khairiana Fitri **Neni Afrida Sari Harahap **Johannes Jefria Gultom Abstract This research was dealt with elicitation techniques used by the teacher in English Classroom Interaction. The objectives of this study were (1) to identify the subcategory of elicitation techniques used by the teacher in English classroom interaction at SMKN 13 Medan (2) to find out the reasons which affect the use of elicitation techniques in English classroom interaction at SMKN 13 Medan. A descriptive qualitative design was used in this study. The data were collected by recording the utterances of teacher. The data were analyzed by data condensation, data display, conclusion drawing/verification. (1) There were 259 elicitations used by the teacher in the classroom interaction. The subcategories that have been found in teacher utterances are elicitation for information, elicitation for confirmation, elicitation for agreement, elicitation for commitment, elicitation for repetition, and elicitation for clarification. (2) For the reasons which affect the use of elicitation techniques. There were six reasons, they were lack of skill and knowledge of teacher, lack confidence of students in class participation, passive recipient of information, reluctant students, large class size, and low level of learners. Meanwhile, the short duration of class and late arrival of students in class were not the reasons which affect the use of elicitation techniques. Keywords : Teachers’ Elicitation Techniques , Classroom Interaction, DescriptiveQualitative.